2021
DOI: 10.1182/blood.2021012732
|View full text |Cite
|
Sign up to set email alerts
|

Novel NPM1 exon 5 mutations and gene fusions leading to aberrant cytoplasmic nucleophosmin in AML

Abstract: Nucleophosmin (NPM1) mutations in acute myeloid leukemia (AML) affect exon 12, but sporadically also exon 9 and 11, all causing changes at protein C-terminal end (loss of tryptophans and creation of a nuclear export signal-NES motif) that lead to aberrant cytoplasmic NPM1 (NPM1c+), detectable by immunohistochemistry. Combining immunohistochemistry and molecular analyses in 929 AML patients, we found non-exon 12 NPM1 mutations in 5/387 (1.3%) NPM1c+ cases. Besides mutations in exon 9 (n=1) and exon 11 (n=1), no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
(34 reference statements)
3
30
0
Order By: Relevance
“…Of note is that a NPM1-CCDC28A fusion transcript has been recently described in an adult patient whose features, however, resembled more an NPM1-mutated AML than APL ( 93 ). The similarities between APL and NPM1-mutated AML will be discussed in the dedicated paragraph.…”
Section: Pathogenesis Characteristics and Management Of Apl Variantsmentioning
confidence: 99%
“…Of note is that a NPM1-CCDC28A fusion transcript has been recently described in an adult patient whose features, however, resembled more an NPM1-mutated AML than APL ( 93 ). The similarities between APL and NPM1-mutated AML will be discussed in the dedicated paragraph.…”
Section: Pathogenesis Characteristics and Management Of Apl Variantsmentioning
confidence: 99%
“…have shown that the NPM1/RPP30 complex serves as one of three NPM1 rearrangements that have been found and analyzed in 13,979 AML samples ( 64 ). In patients with AML that have a NPM1 rearrangement, RPP30 is rearranged with NPM1 at exon 11, whereas the rearrangement of NPM1 with RPP30 is at the end of exon 9 ( 64 ). These data indicate RPP30 may help detect AML and monitor NPM1-mutated AML.…”
Section: Relationship Between Rpp30 and Diseasementioning
confidence: 99%
“…Therefore, the vast majority of amplicon‐based assays currently used in clinical laboratories are designed to target the mutational hotspots in exon 12. However, emerging evidence suggests that other mutations besides the canonical exon 12 mutations may contribute to aberrant NPM1 cytoplasmic localization [ 5 ].…”
Section: Tablementioning
confidence: 99%